Regression Test Suite Management using Data Clustering Technique - Khan, Fayaz Ahmad (International Journal of Computer Sciences and Engineering, 2025)
To test the modified code, we employ regression testing procedures with an aim to provide assurance that modified code behaves correctly and those modifications have not adversely affected the existing behavior or functionality of the code. Retest-all regression testing is the basic approach in which all the test cases in the initial test suite are re-executed to validate the changes. But re-running all the test cases from an existing test suite in order to test the code that is undergone minor change may be expensive as it requires an unacceptable amount of time and resources to perform it. An important problem found during regression testing is how to select a subset of test cases from an existing test suite in order to retest the modified code. Therefore, in this study we propose an efficient test suite management technique that utilizes data clustering approach for regression testing in order to effectively partition an initially random and large test suite to re-test the modified section of the code that has been modified within resource and time constraints